Malthus living in a slum: Urban concentration, infrastructures and economic growth - David Castells-Quintana; Vicente Royuela (European Regional Science Association (ERSA), 2014)
Today more than half of the 7 billion inhabitants of the planet live in urban areas, with this share expected to keep rising. Whereas in developed countries urbanisation has been a long and slow process, in developing countries this process is now characterised by a really fast pace and a high degree of urban concentration, with urban population tending to concentrate in one or few large metropolitan areas of disproportionate size. While urbanisation has been long recognised as a fundamental element of the process of economic development, sustainable urbanisation has become one of the main and more pressing challenges for developing countries, where millions live lacking adequate access to basic services like electricity, clean water and sanitation. Building on previous evidence on urban concentration and economic growth, in this paper we analyse differentiated effects of urban concentration on national economic performance. In order to do so, we rely on panel data from 1960 to 2010 and perform several estimation techniques including System GMM and IV estimations (using rainfall data in the instrumentalisation strategy). We contribute to the literature by providing empirical evidence on how different characteristics of the urban environment - in particular the quality of urban infrastructure - strongly determine the growth-enhancing benefits of urban concentration (something that previous studies on urban concentration and economic growth have not considered empirically). We analyse several measures of urban infrastructure and look at different world regions, taking a special focus on Sub-Saharan African countries, where find that urban concentration has been in most cases associated with lower growth due to significant deficiencies in terms of urban infrastructure.
Keywords: O1; O4; R1; 330; Agglomeration; urbanisation; urban concentration; infrastructure; congestion diseconomies; growth; Sub-Sahara Africa